STUDIES ON FISH EGGS AND LARVAE FROM INDIAN WATERS 2. DEVELOPMENT OF EGG AND LARVAE OE ACENTROOOBIUS ORNATUS (RtFPPELL) - Vijayaraghavan, P (Indian Journal of Fisheries, 2011)
Eggs of Acentrogobius ormtus (Riipp.), attached to Placenta shells were collectedalong with the parent (male) fish guarding it in knee deep water from the Vellar estuaryat Portonovo. The embryonic development from the blastoderm stage up to hatchingand the larvae up to the seventh day are described.Besides the present account on A. ornatus, the eggs and early development of itscongeners, ^ . n«7/i and/4. v/»-/uncra/«;s have been known. The eggs of